Pengaruh Service Excellence Dan Relationship Marketing Terhadap Loyalitas Konsumen Pada Cv Bersinar Pematangsiantar - Jesika Melina Simamora (Strategic: Journal of Management Sciences, 2021)
This study aims to determine The Effect of Service Excellence and Relationship Marketing on Consumer Loyalty in CV Bersinar Pematangsiantar City. The data used in this study are primary data with a sample of 55 people in the CV Bersinar Pematangsiantar City with data collection techniques using questionnaires. The data analysis model used is simple multiple regression with the SPSS v 24 software program for windows. While the conformity test is done using R-Square, Partial Test and Classical Assumption Test. The results of the study found that the regression coefficient on the Service Excellence and Relationship Marketing variable (0.623) means that Service Excellence and Relationship Marketing by 1 point, the Consumer Loyalty (Y) will increase by 0.623. Signs (+) indicate a positive and significant Service Excellence and Relationship Marketing and Consumer Loyalty, is if Service Excellence and Relationship Marketing, Consumer Loyalty will also increase. Keywords: Service Excellence, Relationship Marketing, Consumer Loyalty